Expert-Performed Endotracheal Intubation-Related Complications in Trauma Patients: Incidence, Possible Risk Factors, and Outcomes in the Prehospital Setting and Emergency Department - Yuko Ono; Takeyasu Kakamu; Hiroaki Kikuchi; Yusuke Mori; Yui Watanabe; Kazuaki Shinohara (Emergency Medicine International)
The aim of this study was to determine complication rates and possible risk factors of expert-performed endotracheal intubation (ETI) in patients with trauma, in both the prehospital setting and the emergency department. We also investigated how the occurrence of ETI-related complications affected the survival of trauma patients. This single-center retrospective observational study included all injured patients who underwent anesthesiologist-performed ETI from 2007 to 2017. ETI-related complications were defined as hypoxemia, unrecognized esophageal intubation, regurgitation, cardiac arrest, ETI failure rescued by emergency surgical airway, dental trauma, cuff leak, and mainstem bronchus intubation. Of the 537 patients included, 23.5% experienced at least one complication. Multivariable logistic regression analysis revealed that low Glasgow Coma Scale Score (adjusted odds ratio [AOR], 0.93; 95% confidence interval [CI], 0.88–0.98), elevated heart rate (AOR, 1.01; 95% CI, 1.00–1.02), and three or more ETI attempts (AOR, 15.71; 95% CI, 3.37–73.2) were independent predictors of ETI-related complications. We also found that ETI-related complications decreased the likelihood of survival of trauma patients (AOR, 0.60; 95% CI, 0.38–0.95), independently of age, male sex, Injury Severity Score, Glasgow Coma Scale Score, and off-hours presentation. Our results suggest that airway management in trauma patients carries a very high risk; this finding has implications for the practice of airway management in injured patients.